Modelling and Control of Mechatronic and Robotic Systems - Gasparetto, Alessandro; Seriani, Stefano; Scalera, Lorenzo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Currently, the modelling and control of mechatronic and robotic systems is an open and challenging field of investigation in both industry and academia. The book encompasses the kinematic and dynamic modelling, analysis, design, and control of mechatronic and robotic systems, with the scope of improving their performance, as well as simulating and testing novel devices and control architectures. A broad range of disciplines and topics are included, such as robotic manipulation, mobile systems, cable-driven robots, wearable and rehabilitation devices, variable stiffness safety-oriented mechanisms, optimization of robot performance, and energy-saving systems.